2004
DOI: 10.1016/j.scitotenv.2003.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Formation of PCDD/Fs from heating polyethylene with metal chlorides in the presence of air

Abstract: This paper investigated the effect of inorganic chlorine on the formation of PCDDyFs from heating polyethylene (PE) in the presence of air. There was an increase in the formation of PCDDyFs with an increasing amount of metal chlorides except NaCl, which was not observed to have any effects on the formation of PCDDyFs without the presence of catalysts. Although the levels of PCDDyFs formation in this study have no relevance to full scale municipal solid waste incineration, the results of the present experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The mechanism of the conversion of the chlorine in NaCl into gaseous HCl is very well understood. The first step involves reaction of NaCl with the wet SiO 2 and/or Al 2 O 3 , forming a complex of sodium-silico-aluminates and HCl [133]. The most important factors in the conversion process are the availability of water vapour, the presence of zeolite, silica, alumina or clay minerals in the ash and the incinerator's temperature and design.…”
Section: Chlorine Speciation In the Gas Phasementioning
confidence: 99%
“…The mechanism of the conversion of the chlorine in NaCl into gaseous HCl is very well understood. The first step involves reaction of NaCl with the wet SiO 2 and/or Al 2 O 3 , forming a complex of sodium-silico-aluminates and HCl [133]. The most important factors in the conversion process are the availability of water vapour, the presence of zeolite, silica, alumina or clay minerals in the ash and the incinerator's temperature and design.…”
Section: Chlorine Speciation In the Gas Phasementioning
confidence: 99%
“…The fly ash surface bonding forms surface-active material to adsorb precursor materials, and the complicated precursor condensation reaction is formed by catalyzing metals to form PCDD/Fs. (Zheng et al, 2004;Ryu, 2008;Liu et al, 2011). The degradation of carbon structures forms small molecule substances, and then the interaction forms PCDD/Fs (Lundin and Marklund, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For CP3, the gas emitted from charging of the coal was conducted into the adjacent combustion chambers, which might result in very low emission level of the dioxins. It was reported that the composition of raw materials in thermally related processes had significant influence on dioxins formations and emissions (Tuppurainen et al, 1998;Hatanaka et al, 2000;Wikström and Marklund, 2001;Wikstörm et al, 2003;Wang et al, 2003;Zheng et al, 2004). Therefore, the contents and forms of some elements in coal used for coke production, such as chlorine, copper, and sulfur, are supposed to also affect dioxin emissions.…”
Section: Resultsmentioning
confidence: 99%